Islamic finance, governance and regulation : global perspectives - Hakimah Haji Yaacob; Razali Mat Zin; Qaisar Ali (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Islamic financial institutions (IFIs) are often criticized due to insufficient regulatory provision, thus lowering clients' confidence in them. Additionally, few countries have well-established legislation relating to the Islamic finance industry, while others are only now developing preliminary regulations to incorporate Islamic finance within their own financial systems. This book offers a comprehensive understanding of Islamic financial regulation, outlining the regulatory landscape in various jurisdictions, examining how it supports the development and foundation of IFIs and addressing the regulation and supervision of IFIs from a global perspective. The book begins by introducing Islamic finance and its current position in the international banking system, then goes on to review the historical developments of the field. It discusses the key financial regulators, their functions, and the regulations that have been implemented to foster the growth of Islamic finance. It includes cases from both Eastern and Western countries. It thoroughly examines how Shariah principles are integrated into the regulatory framework of Islamic finance. Specifically, the book examines the laws and arrangements established in different countries regarding the governance of the Islamic finance industry as well as the legal criteria for setting up and governing IFIs. The focus is on exploring diverging laws and their impact on developing Islamic Finance. This will serve as an academic and practitioner guide to understanding the preliminary regulations required for the establishment, governance, and management of IFIs. Also, it offers practical insights and guidance for professionals working in the Islamic finance industry, including bankers, lawyers, regulators, and policymakers"--
Global finance and Islamic financial system -- Islamic financial regulations in ASEAN -- Islamic financial jurisdictions in South Asia -- Islamic finance in Central Asia -- Islamic financial jurisdictions in East Asia -- Islamic financial regulations in the Middle East -- Islamic financial regulations in Africa -- Regulatory framework of financial institutions in Europe -- Financial regulations in Australia and North America.
Keywords: Finance -- Islamic countries; Finance -- Religious aspects -- Islam; Finance (Islamic law); BUSINESS & ECONOMICS / Banks & Banking; LAW / Banking